Sustainable management of the swiftlet ranching industry in Johor Bahru and Gua Musang, Malaysia - Alpandi, Rabiatul Munirah (2018)
The rise in the number of swiftlet ranches leading to a year-on-year rise in EBN production is testament to the beguiling market demand. However the industry faces a major hurdle where 70 percent to 80 percent of swiftlet ranches are regarded as inefficient since failed to achieve 1.36kg of nest after one year of operation due to a lack of understanding and knowledge in the management of swiftlet ranching. In order to boost the production of EBN, the level of total management efficiency of swiftlet ranches in Johor Bahru and Gua Musang has been measured using the Data Envelopment Analysis (DEA). The results reveal that the efficiency of management inputs (electricity, water irrigation, human labour and pesticides) are more important than the scale or size in both areas. The DEA results also suggest that there are a total of 15 efficient ranchers in both areas that can be as benchmarked for inefficient ranchers. From the empirical results of the Tobit regression, the usage of planks, water irrigation and labour are important determinants that can influence total management efficiency in Johor Bahru while size of swiftlet ranch and water irrigation are important determinants in Gua Musang. By applying the DEA method its not only can help to improve the level of management of swiftlet ranch but also can improve the environment practice with an optimum input energy level for only 18.04MJ and 9.81MJ was required for Johor Bahru and Gua Musang respectively. As such, the total energy that could be potentially be saved at 286.69% and 700.14% for Johor Bahru and Gua Musang respectively. Other than that, the management of swiftlet ranch also can be improve by maps out the social network of swiftlet ranching in Johor Bahru and Gua Musang in order to capture the main stakeholders that can play an important role for knowledge sharing regarding the management of swiftlet ranch. In Johor Baharu and Gua Musang Rancher 3 and Rancher 21 have higher indegree relationships where known as the higher knowledge collector in the network, while for out degree relationship, Rancher 2 and DV1 are the main stakeholder that can play role as given information regarding management of swiftlet ranches. However base on the result centralization closeness 36.52% in Johor Bahru and 39.92% in Gua Musang showing that the knowledge sharing inside both networks are subdued. All this important stakeholder need to be highlight since any information and policy to improve the management of the swiftlet ranch can be seen through these actors or stakeholders to ensure the industry becomes more successful in the future.